Hidden Ray-Tracing on the Shadow Boundary of Penetrable Wedges - Kim, S.-Y. (Proceedings of the 2018 20th International Conference on Electromagnetics in Advanced Applications, ICEAA 2018, 2018)
Diffraction coefficients of penetrable wedges are constructed analytically by employing the hidden rays of diffraction. The conventional ray-tracing on the lit boundary of a lossy dielectric wedge is performed until the multiple reflections inside the wedge are terminated. The last ordinary ray reflected from one lit boundary evolves into the first hidden ray incident on the other shadow boundary. The hidden ray-tracing in the complementary region is continued until the hidden ray cannot evolve again into an ordinary ray in the physical region. The diffraction coefficients of a lossy dielectric wedge constructed routinely from the hidden ray-tracing data reveal more accurate than the physical optics solution. ？ 2018 IEEE.